14-3-3 γ-isoform detection distinguishes sporadic Creutzfeldt–Jakob disease from other dementias. Issue 1 (16th December 2004) - Van Everbroeck, B R J; Boons, J; Cras, P
Abstract : We developed a polyclonal antiserum directed to the γ-isoform of the human 14-3-3 protein and compared the immunoreactivity with a commercially available antibody (CG31). We analysed 14-3-3 in 253 cerebrospinal fluid samples blinded for the diagnosis by western blot and ELISA, with a commonly used polyclonal antiserum (Sc-731) and the γ specific antibodies. Our patient population consisted of 52 patients with definite sporadic Creutzfeldt–Jakob disease (sCJD) and 201 patients with a different final diagnosis. We obtained similar sensitivity, ranging from 96% to 98% with all antibodies. Of all the samples that were false positive with Sc-731, 50% were negative with both γ-isoform specific antibodies resulting in a significantly higher specificity (85% v 93%, respectively). If only sCJD and patients with dementia differing from sCJD were analysed we found that 64% of false positives were negative which also resulted in significantly increased specificity and positive predictive value. The γ-isoform specific antibodies strongly improve the specificity of the immunoblot and might improve worldwide acceptance of the use of the 14-3-3 assay in the differential diagnosis of sCJD.